The Influence of Social Media Marketing Strategy on Consumer Trust in Makeup Artist Services (A Case Study on Makeup by Arra) - Fitryansyah, Alya; Barusman, Andala Rama Putra (The Eastasouth Management and Business, 2025)
The reason of this consider is to evaluate the affect of advanced promoting procedures, such as content-based showcasing, social media utilize, social media calculations, and gathering of people interaction, on client fulfillment and customer certainty in Cosmetics by Arra administrations. The approach is quantitative, utilizing Basic Condition Modeling (SEM). Inshaping were collected through a web survey including 248 respondents, chosen utilizing the purposive testing method. The discoveries demonstrate that social media and intuitive with gatherings of people have a positive and noteworthy affect on client fulfillment. Moreover, client fulfillment acts as a interceding figure within the interrelation between social media and gathering of people interaction and shopper certainty levels. In differentiate, content-based showcasing methodologies and the operation of social media calculations have no noteworthy impression on client fulfillment or shopper certainty. This research concludes that social media and audience interaction have a leading role in building consumer confidence in the services offered. The findings recommend Makeup by Arra to improve interactive marketing strategies via social media to strengthen connections with consumers and strengthen their trust. This ponder analyzes the adequacy of computerized showcasing mechanisms such as content-based promoting and the utilize of social media. Social media and gathering of people interaction calculation and its affect on client fulfillment and shopper certainty Cosmetics by Arra.